A hybrid EDF/FIFO queue for efficient real time flow handling - Fawaz, W. (2006)
In an attempt to meet the stringent time constraints of real time flows, several scheduling algorithms have been proposed in the literature. Among such algorithms, the so-called EDF algorithm is widely known for its optimal management of flows with strict time constraints, when compared with the standard FIFO algorithm. But still, EDF is complex and expensive as far as implementation is concerned. As a main contribution in this paper, we therefore propose a hybrid EDF/FIFO queue management approach, which consists of a short EDF queue completed by a FIFO queue. This approach allows reducing EDF’s implementation complexity while making efficient use of its optimal flow management. Our simulation results underscore the main interest behind this proposal.